Religion and diversity in Canada - Beaman, Lori G.; Beyer, Peter, 1949- (Religion and the Social Order, 2008)
Canada officially prides itself on being a multicultural nation, welcoming people from all around the world, and enshrining that status in its Charter of Rights and Freedoms as well as in an array of laws and policies that aim to protect citizens from discrimination on various grounds, including race, cultural origin, sexual orientation, and religion. This volume explores the intersection of these diversities, foregrounding religion as the primary focus of analysis. Taking as their point of departure the contested meaning and implications of the term diversity, the various contributions address issues such as the power relations that diversity implies, the cultural context that limits the understanding and practical acceptance of religious diversity, and how Canada compares in these matters to other countries. Taken together the essays therefore elucidate the Canadian case while also having relevance for understanding this critical issue globally.